Distinctive Labeling of Live Monocytes and Neutrophils with a Single Fluorescent Molecule - Songhui Kim; Masahiro Fukuda; Jung Yeol Lee; Young-Tae Chang; H. Shawn Je; Beomsue Kim (Chemosensors, 2023)
(1) Background: a small-molecule fluorescent chemosensor, CDr20, tracks the resident macrophages based on the UGT1A7C activity in the brain, raising the possibility that additional immune cells expressing the UGT1A7C can be labeled with CDr20. (2) Methods: we applied CDr20 to various types of blood cells derived from hematopoietic organs (spleen and bone marrow) as well as peripheral blood to test the degree and selectivity of labeling of CDr20 in these cell types; (3) Results: CDr20 fluorescently labels monocytes/macrophages and neutrophils as a result of glucuronidation reaction (CDr20-Gluc), which is mediated with UGT1A7C. The selectivity of CDr20 labeling highly correlates with the Ugt1a7c expression level in immune cells. Moreover, CDr20-Gluc is exported from cells by a mechanism of how glucuronides within cells are excreted into extracellular space. Interestingly, the exportation of CDr20-Gluc is mainly observed in monocytes, potentially due to the monocyte-specific expression of ABCC transporters and this resulted in large differences in the degree of fluorescence retention in neutrophils (CDr20bright), compared to monocytes (CDr20dim) upon one hour of CDr20 incubation; (4) Conclusions: CDr20 can differentially label monocytes and neutrophils due to the variance in two different cellular enzymatic activities of UGT1A7C and ABCC. By using this property, CDr20 can be used to distinguish specific cell types within blood.